2020
DOI: 10.1111/ede.12356
|View full text |Cite
|
Sign up to set email alerts
|

Whispers from vestigial nubbins: Arrested development provokes trait loss in toads

Abstract: Despite the use of acoustic communication, many species of toads (family Bufonidae) have lost parts of the tympanic middle ear, representing at least 12 independent evolutionary occurrences of trait loss. The comparative development of the tympanic middle ear in toads is poorly understood. Here, we compared middle ear development among two pairs of closely related toad species in the genera Atelopus and Rhinella that have (eared) or lack (earless) middle ear structures. We bred toads in Peru and Ecuador, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Neither study found consistent phenotypic differences between eared and earless species. Other studies have investigated whether tympanic middle ear loss is a side effect of changes in developmental timing or rate (heterochrony), but none have found consistent shifts in development among earless species [77,[82][83][84]. However, these studies did not exhaustively quantify earless species phenotypes, making it possible that a shared developmental or phenotypic change exists among earless taxa.…”
Section: Is Tympanic Middle Ear Loss the Results Of Genetic Or Develo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Neither study found consistent phenotypic differences between eared and earless species. Other studies have investigated whether tympanic middle ear loss is a side effect of changes in developmental timing or rate (heterochrony), but none have found consistent shifts in development among earless species [77,[82][83][84]. However, these studies did not exhaustively quantify earless species phenotypes, making it possible that a shared developmental or phenotypic change exists among earless taxa.…”
Section: Is Tympanic Middle Ear Loss the Results Of Genetic Or Develo...mentioning
confidence: 99%
“…However, these studies did not exhaustively quantify earless species phenotypes, making it possible that a shared developmental or phenotypic change exists among earless taxa. Given the nearly unlimited potential pleiotropic connections between the tympanic middle ear and other traits, genetic scans for mutations associated with tympanic middle ear loss and comparative developmental studies that examine changes during the window of arrested tympanic middle ear development [77] would allow a more thorough examination of this hypothesis.…”
Section: Is Tympanic Middle Ear Loss the Results Of Genetic Or Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous anuran clades have vestigial middle structures, in which some earlier developing structures of the middle ear remain (Pereyra et al, 2016) but seemingly lack any hearing‐related function (Womack et al, 2018). Other middle ear loss clades have transient middle ear structures during development but completely lack middle ear structures as adults (Stynoski et al, 2020). Even within a population, some individuals show no trace of the middle ear as adults and others have small cartilaginous chunks of middle ear bone as adults (Stynoski et al, 2020).…”
Section: Examining the Developmental Continuum Of Inter‐ And Intraspecific Trait Losses Reveals Evolutionary Rules/axes Of Variationmentioning
confidence: 99%
“…Other middle ear loss clades have transient middle ear structures during development but completely lack middle ear structures as adults (Stynoski et al, 2020). Even within a population, some individuals show no trace of the middle ear as adults and others have small cartilaginous chunks of middle ear bone as adults (Stynoski et al, 2020). Similarly, forelimbs, hind limbs, and pelvic bones have been convergently lost to varying degrees among skink species with additional intraspecific variation in the degree of loss noted in some lineages (Moch & Senter, 2011).…”
Section: Examining the Developmental Continuum Of Inter‐ And Intraspecific Trait Losses Reveals Evolutionary Rules/axes Of Variationmentioning
confidence: 99%